2002
DOI: 10.1063/1.1496472
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and ab initio investigation of the O–H overtone vibration in ethanol

Abstract: The effect of weak interactions on the ring puckering potential in the coumaran-argon van der Waals complex: Experimental and ab initio analysis of the intermolecular and low-frequency intramolecular vibrations Ab initio determination of the far infrared spectra of some isotopic varieties of ethanolThe intracavity dye laser photoacoustic absorption spectra of ethanol, ethanol (1,1-d 2 ), and ethanol (2,2,2-d 3 ) are reported for the region 16 550-16 700 cm Ϫ1 , which contains the O-H fourth overtone (⌬ OH ϭ5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…At higher temperature, the thermal agitation energy kT has a value of about 1.3 kcal/ mol comparable to the energy of the torsional barrier estimated for analogous simpler alcohols in gaseous phase. 27 As a consequence, the rotation around the C-O axis can be considered as free and different conformers cannot be recognized. The band shape is governed this time by the ␤-␣ equilibrium, for which the population of ␣ groups is no more negligible.…”
Section: Data Processing Of Mir and Nir Spectramentioning
confidence: 99%
“…At higher temperature, the thermal agitation energy kT has a value of about 1.3 kcal/ mol comparable to the energy of the torsional barrier estimated for analogous simpler alcohols in gaseous phase. 27 As a consequence, the rotation around the C-O axis can be considered as free and different conformers cannot be recognized. The band shape is governed this time by the ␤-␣ equilibrium, for which the population of ␣ groups is no more negligible.…”
Section: Data Processing Of Mir and Nir Spectramentioning
confidence: 99%
“…The empirical substitution (r s ) structure has been determined by microwave spectroscopy [138,139]. The overtone spectrum was measured by Fang et al [140], Lange et al [141], Weibel et al [142], and Hu et al [143] up to v OH ¼ 6. From their work, it is possible to derivẽ !…”
Section: Ethanolmentioning
confidence: 99%
“…Senent et al [15] used Dunning's correlation consistent triple zeta basis set with Møller-Plesset perturbation theory up to MP4 and obtained the anti form falling 19 cm -1 below the gauche form. Weibel et al [16] have carried out a number of higher-level ab initio calculations including coupled cluster calculations, and found that both MP4 and CCSD(T) single-point calculations place the gauche form about 0.13 kcal/mol below the anti form. These workers also noted that the narrower potential well for the gauche torsion results in a zero-point energy larger by about 113-125 cm -1 for this form, which can reverse the order.…”
Section: Introductionmentioning
confidence: 99%